Digital Marketing: Optimization of Uniwara Pasuruan Students to Encourage UMKM "Jamu Kebonagung" Through Branding Strategy - Aziz Wisnu Aryaseta; Ilmiyatur Rosidah; Viona Eka Cahaya; Jangky Dausat; Rani Darmayanti (Jurnal Dedikasi, 2023)
Pasuruan is a city in the eastern part of Java Island, famous for its traditional drink brand, "Jamu Kebonagung." Spices' distinctive taste and benefits as the main ingredient make this drink very popular. Economic demands make people try their luck in participating in market competition by making and marketing other products to survive during economic pressures. One of the oldest UMKM in Pasuruan does something different: one of the many micro and small businesses that can support the economy of small communities and remain loyal and continue to manage and produce while maintaining taste. There are obstacles in marketing these products, especially in the current era of digitalization. As a result, UMKM needs help in running their businesses. Uniwara students in this KKN activity provided solutions by providing community service and training regarding product branding in digital marketing